Biblical discourses and the subjugation of Africa: A Decolonial-Foucauldian perspective - T. Shingange (Acta Theologica)
The Western missionaries and colonialists pushed a similar agenda of subjugating the receptor’s core aspects of life. Among their targets were aspects of culture, religion, gender, and sexuality. This trend continues in the contemporary era within different global spaces. In Africa, the Americas, and Asia, missionaries promulgated colonial ideologies through the transmission and reception of biblical discourses. This was done under the guise of civilisation, Christianisation, and evangelisation of Africans who were and are still perceived and portrayed as primitive, savages, and pagans. This article argues that biblical resources served as modalities of power in the colonial subjugation agenda. The article uses the transmission and reception of biblical discourses as lenses for examining how coloniality targeted these aspects. The de-colonial motif was used to problematise these discourses. On the other hand, Foucault’s perspective on discourses and power shed some light on how colonial power dynamics were at play in this context. A clarion call was then made to shift Christianity’s centre of power from the Northern continents to the South.